Biofortification: Concept and Methodologies - Baum, Michael; Tiwari, Vandita; Meenu, Maninder; Khandare, Kiran; Sheoron, Bhawna; Kaur, Satveer; Yadav, Mona (CRC Press, 2024)
In life, a well-balanced diet is of utmost importance. A well-balanced diet can provide essential nutrients for good human health, including a wide array of micronutrients. Most of the global population relies on staple crops like rice, wheat, maize, sorghum, millets, and root and tuber crops for nutrition. Due to an insufficient supply of proteins, vitamins, and minerals from the available food sources, one-half of the world’s population is suffering from malnutrition. Traditionally, nutrient shortages were addressed via supplementation and fortification. Contemporary times necessitate novel strategies to reach underserved rural communities, effectively managing the hurdles of micronutrient malnutrition. The alternative solution, namely, biofortification, is serving to meet nutritional needs. Biofortified crops have a higher content of targeted nutrients in the edible part of plants. This chapter explores the significance and fundamental principles of biofortification and highlights agronomic, plant breeding, and transgenic-based approaches used for this purpose. Moreover, we delve into the challenges linked with biofortification.